Exploring well-being as a tourism product resource. (August 2016) - Pyke, Sarah; Hartwell, Heather; Blake, Adam; Hemingway, Ann
Abstract: This study employs a qualitative research approach where focus groups (n = 11) with key stakeholders were used to understand how tourism investors view the concept of well-being in relation to tourism and the potential to use it as a tourism product resource. Findings validated by a wider group (n = 50) exposed the barriers and enablers of implementing well-being in this way. The potential for businesses and policymakers to transform these barriers into enablers was also identified. In addition, study findings were mapped onto a robust model extracted from the public health sector and applied in a tourism context using a systems theory approach. This further highlighted the potential offered to the fields of public health and tourism in the concept of well-being, and demonstrated the well-being value of tourism. Data from this research will aid tourism business practice and development by embedding a well-being philosophy for tourism destinations' strategies. Highlights: Tourism and public health sectors are merging around the concept of well-being. Stakeholder views on using well-being as a tourism product resource are explored. Barriers and enablers of implementing well-being into tourism strategy are outlined. The potential to transform the identified barriers into enablers is discussed. Findings are mapped onto a public health model and applied in a tourism context.